2019
DOI: 10.32539/bsm.v3i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Cinnamon Extract (Cinnamomum burmannii) against Staphylococcus aureus and Escherichia coli In Vitro

Abstract: Abstract   Infectious disease is one of the most common diseases in the world. Staphylococcus aureus and Escherichia coli are two common causes of infection and are resistant to many antibiotics, so the new agents are needed to overcome antibiotic resistance. Cinnamon is often used as a preservative because it has antibacterial activity. Cinnamomum burmannii is kind of native cinnamon from Indonesia. The antimicrobial active compounds cinnamaldehyde and eugenol are the main reasons for its antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
0
7
0
4
Order By: Relevance
“…The results of the study also found that the extract concentration of cinnamon bark 10% to 40% had a strong inhibition against Gram-positive bacteria. 12 The result of Kruskal Walis Test obtained p = 0,000321 (p <0.05), which means that there are significant differences in inhibition zone diameter at various concentrations of cinnamon bark extract. This is consistent with the research hypothesis which states that there are effects of various concentrations of cinnamon extract from the growth of Lactobacillus acidophilus as seen from the diameter of two inhibitory zones.…”
Section: Discussionmentioning
confidence: 92%
“…The results of the study also found that the extract concentration of cinnamon bark 10% to 40% had a strong inhibition against Gram-positive bacteria. 12 The result of Kruskal Walis Test obtained p = 0,000321 (p <0.05), which means that there are significant differences in inhibition zone diameter at various concentrations of cinnamon bark extract. This is consistent with the research hypothesis which states that there are effects of various concentrations of cinnamon extract from the growth of Lactobacillus acidophilus as seen from the diameter of two inhibitory zones.…”
Section: Discussionmentioning
confidence: 92%
“…Extract than concentrated by vacuum rotary evaporator. Cinnamon bark extract the further evaluated by phytochemical screening, using standard procedure [11].…”
Section: Preparation Of Cinnamon Bark Extractmentioning
confidence: 99%
“…The main chemical content of essential oil from cinnamon is Cinnamaldehyde (Fajar et al 2019), amounting to 83.65% (Tokan et al 2019). The components of these essential oils have antibacterial activity against Escherichia coli and Staphylococcus aureus (Parisa et al 2019), which are the causes of diarrhea. Cinnamaldehyde has the potential to be developed as an antibiotic to treat diarrhea (Tokan et al 2019).…”
Section: The Commercial Prospects For the Three Species Cinnamomum Burmannimentioning
confidence: 99%